More Unfinished Business - Plauṭ, Zeʾev Mosheh 1912-2012 (University of Toronto Press, 2016)
More Unfinished Business is a companion to the first volume of Rabbi Plaut?s 1981 memoir, Unfinished Business, offering readers his reflections on the unfolding of his life and work, and of events that touched him, during the past two decades. In some of these events ? for instance, in the case of his report on refugee policy and his role in shaping the direction of the Reform movement in Judaism, his reach has touched the lives of many thousands of people. This is a book of doings and musings rather than a detailed analysis of events. Rabbi Plaut considers how the events and issues he was involved with forced him to confront and reassess his life?s work, his religious, institutional, and political commitments. To understand this process, the reader is invited to consider something of the private man behind the events. It is this effort to reveal himself as a person, rather than as an actor in history, that gives added meaning to his reminiscences and his discussion of his concerns, involvements, and disappointments ? wrestling with prayer, the future of Judaism, ageing and mortality, parting with material possessions, even his passion for tennis.Rabbi Plaut is an exceptional writer and story-teller. This is a remarkable book by a remarkable man